UTILIZATION OF ACTIVATED ZEOLITE AS MOLECULAR SIEVE IN CHROMATOGRAPHIC COLUMN FOR SEPARATION OF COAL TAR COMPOUNDS - Dwi Retno Nurotul Wahidiyah; Bambang Setiaji; Iqmal Tahir (Indonesian Journal of Chemistry, 2004)
Application of activated zeolite (ZAA) as molecular sieve to separate compounds of coal tar from vaccum fractional distillation, have been done. The size of zeolite was 10-20 mesh and used as solid phase in column chromatography with length of 30 cm. The first step of the research was coal pyrolisis and the product (tar) was distillated by fractional column and vaccum system at reduced pressure 44 cmHg and maximum temperature at 200 oC. The distillate from this procedure was flowed to the column chromatography of zeolite (ZAA). The compound absorbed by zeolite was eluted with varying solvents, i.e: CCl4, acetone and ethanol. Each fraction was then analyzed by gas chromatography. The results showed, zeolite have a capability to separate the compounds of tar and it tends to absorb medium hydrocarbon. The nonpolar eluent [CCl4] gives the better result in eluting tar compound than polar (ethanol) or medium polar eluents (acetone).